2021
DOI: 10.1186/s13213-021-01622-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety assessment of Lactobacillus reuteri IDCC 3701 based on phenotypic and genomic analysis

Abstract: Purpose Lactobacillus reuteri is one of the most largely studied human-commensal bacteria and widely used as a form of probiotics. Safety of probiotics has become increasingly important for human consumption due to increasing health-concerns in food industry. In this study, the safety of L. reuteri IDCC 3701 isolated from human breast milk was thoroughly investigated. Methods Whole-genome sequence analysis was performed to identify antibiotic resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…BL produced more l ‐lactate than d ‐lactate: 17.37 mg/mL of l ‐lactate (82.87%) and 3.59 mg/mL of d ‐lactate (17.13%). The value of d ‐lactate formation and the ratio of d ‐ to l ‐lactate were much lower than those of other lactic acid bacteria such as L. plantarum , L. acidophilus , L. reuteri , and L. delbrueckii (Bang et al, 2021 ; Lee et al, 2021 ; Sulemankhil et al, 2012 ). In particular, L. reuteri NCIMB 30253 and L. delbrueckii ATCC 11842 produced higher ratios of d ‐lactate than l ‐lactate, with 6:5 and 12:11 ratios of d ‐ to l ‐lactate, respectively (Sulemankhil et al, 2012 ).…”
Section: Resultsmentioning
confidence: 94%
“…BL produced more l ‐lactate than d ‐lactate: 17.37 mg/mL of l ‐lactate (82.87%) and 3.59 mg/mL of d ‐lactate (17.13%). The value of d ‐lactate formation and the ratio of d ‐ to l ‐lactate were much lower than those of other lactic acid bacteria such as L. plantarum , L. acidophilus , L. reuteri , and L. delbrueckii (Bang et al, 2021 ; Lee et al, 2021 ; Sulemankhil et al, 2012 ). In particular, L. reuteri NCIMB 30253 and L. delbrueckii ATCC 11842 produced higher ratios of d ‐lactate than l ‐lactate, with 6:5 and 12:11 ratios of d ‐ to l ‐lactate, respectively (Sulemankhil et al, 2012 ).…”
Section: Resultsmentioning
confidence: 94%
“…Noxious enzymes, such as β-glucuronidase, have the capacity to convert procarcinogens to carcinogens through hydrolysis of glycosidic bonds [ 36 ]. The accumulation of D-lactate can occur only in case of gastrointestinal dysfunction, such as D-lactate metabolism disorders, but excessive accumulation of D-lactate in the blood can cause health problems [ 37 ]. Hemolytic activity, usually caused by hemolysin produced by microorganisms, induces lysis of red blood cells leading to infection by pathogens [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the resistance against kanamycin and streptomycin seems to be an intrinsic trait of this strain. Indeed, several studies have shown that several Lactobacillus species, including some commercially used strains, exhibit relative resistance to aminoglycoside antibiotics, such as gentamicin, kanamycin, and streptomycin [ 17 , 23 , 24 ]. As a result, L. fermentum KGC1601 can be considered safe in terms of antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%